Recent advances on small molecular gels: formation mechanism and their application in pharmaceutical fields. (2nd December 2022) - Su, Meiling; Zhang, Jingwen; Li, Zudi; Wei, Yuanfeng; Zhang, Jianjun; Pang, Zunting; Gao, Yuan; Qian, Shuai; Heng, Weili
ABSTRACT: Introduction: As an essential complement to chemically cross-linked macromolecular gels, drug delivery systems based on small molecular gels formed under the driving forces of non-covalent interactions are attracting considerable research interest due to their potential advantages of high structural functionality, lower biological toxicity, reversible stimulus–response, and so on. Area covered: The present review summarizes recent advances in small molecular gels and provides their updates as a comprehensive overview in terms of gelation mechanism, gel properties, and physicochemical characterizations. In particular, this manuscript reviews the effects of drug-based small molecular gels on the drug development and their potential applications in the pharmaceutical fields. Expert opinion: Small molecular-based gel systems, constructed by inactive compounds or active pharmaceutical ingredients, have been extensively studied as carriers for drug delivery in pharmaceutical field, such as oral formulations, injectable formulations, and transdermal formulations. However, the construction of such gel systems yet faces several challenges such as rational and efficient design of functional gelators and the great occasionality of drug-based gel formation. Thus, a deeper understanding of the gelation mechanism and its relationship with gel properties will be conducive to the construction of small molecular gels systems and their future application.